The Influence of Spiritual Leadership on Harmonious Passion: A Case Study of the Hotel Industry in China - Wang, Yingda; Jin, Yixing; Cheng, Lin; Li, Ying (Frontiers in Psychology, 2021)
The hotel manager has the responsibility to stimulate the passion of the staff. The vision, hope/faith and altruistic love advocated by spiritual leaders can meet the independent psychological needs of employees, thus enhancing their harmonious passion. This study is based on self-determination theory, intrinsic motivation theory and psychological capital theory, and explores the relationship between spiritual leadership and employees’ harmonious passion. This study uses 260 employees of star hotels in Beijing, Shanghai, Hangzhou, Hefei, Huangshan and other cities in China. Results show that spiritual leadership positively impacts employees’ harmonious passion, and calling plays an mediation role between spiritual leadership and employees’ harmonious passion. The results are helpful to clarify the formation mechanism of employees’ harmonious passion from the perspective of self-determination theory, intrinsic motivation theory and psychological capital theory and show that spiritual leadership can drive employees’ harmonious passion, especially when hotel vision and employee calling are consistent. Furthermore, the altruistic love of spiritual leaders for their followers also plays a key role in employee calling and promoting harmonious passion. Therefore, this study also emphasises the importance of calling in improving the harmonious passion of employees. The theoretical and management implications that help to enhance the harmonious passion of employees are discussed in detail.